Application of the Component Method to Aluminum Alloy Gusset Joints. Issue 11 (November 2015) - Guo, Xiaonong; Xiong, Zhe; Luo, Yongfeng; Qiu, Liqiu; Huang, Weijia
The stiffness of aluminium alloy gusset (AAG) joints plays a key role in the global buckling behaviour of single-layer reticulated shells. In this paper, the bending stiffness of AAG joints is mainly analysed by using the component method. Based on the M -φ curves obtained from a previous experimental program, a four-linear mathematical model which is used to evaluate the bending stiffness behaviour of AAG joints is proposed. To calculate the four-linear mathematical model, the deformation mechanism of AAG joints is discussed and the component model for the joint bending stiffness is developed. According to theoretical derivations and extensive finite element simulations, the formulae to estimate the whole range bending stiffness of AAG joints are presented. Finally, the applicability of the theoretical formulae is verified by comparing the theoretical results with the experimental results.